(untitled) (Discourse of Law and Administration, 2019)
The constitutional principles can be considered as the foundations of social participation in a democratic state of law. These are the rules that enable citizens to articulate their needs and views, indicate to the authorities directions and ways of resolving in given matters, and thus have a direct impact on the shape of social participation. One of such principles is the principle of civil society, which gives the possibility of public participation in making political, economic and social decisions that are important from the point of view of society in general. The purpose of this article is to present the principle of civil society in normative terms and to show the construction elements of this principle. Although the principle of civil society was not expressed directly in the Constitution of the Republic of Poland of April 2, 1997, it is possible to interpret this principle from a number of its provisions. Such a diversified constitutional basis is undoubtedly due to widely developed legal possibilities, which an entity can use to realize its subjectivity. Therefore, due to the dynamically changing socio-economic and political circumstances, the content of this principle should be subject to continuous interpretation.